Status And Position Of Children Bornin A Valid Marriage According To The Law - Agustin Leni Magdalen Rohi Riwu; Seheslon Killyon Bessie (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Children born in a valid marriage according to the Rote tradition sometimes have their status not recognized in society if the relationship between the parents and the family is not harmonious or if problems occur in the marriage process which has an impact on the child's relationship with the biological father and the father's family. The aim of the research is to determine the status of children and the position of children born in a legal customary marriage according to the customary law of the Rote indigenous community in the inheritance system. The results obtained: giving a dowry (belis) will create a continuous reciprocal relationship between both sides of the family, the status and position of children born in valid marriages according to Rote customary law, because if the relationship between the parents is not harmonious then the child's status is not recognized as the child of the biological father so he cannot claim his rights as an heir. The parties involved have a role and function to make an agreement that does not burden either party, and provides a sense of justice for each party, so that the dispute can be resolved amicably. does not destroy the order of traditional values ​​in society.